The association between body roundness index and mortality in diabetes - Han Liu; Haowen Ye; Xiaofang Zhang; Yun Wen; Jiaxin Wang; Meixin Yu; Xian Yang; Caixia Ma; Liangyan Wu; Yongting Zhao; Lihong Wang (BMC Cardiovascular Disorders)
Abstract Background The association between body roundness index (BRI) and all-cause mortality and the occurrence of cardiovascular disease (CVD) in patients with diabetes is unknown. This study aimed to determine the association between BRI and all-cause/CVD mortality in a diabetic cohort. Methods A total of 8227 individuals with diabetes from the 1999–2018 National Health and Nutrition Examination Survey (NHANES) database were included. Multifactorial Cox regression models were used to analyze the association between BRI and mortality in patients with diabetes. Multivariate-adjusted restricted cubic spline (RCS) regression was used to test for nonlinearity. Results During a median follow-up of 7.25 years, a total of 27.22% died, with 9.18% of these deaths due to CVD. After fully adjusting for potential confounders, BRI remained significantly associated with all-cause/CVD mortality in the diabetic population. The restricted cubic splines revealed no significant nonlinear relationship between BRI and all-cause mortality (P = 0.29) or CVD mortality (P = 0.73). BRI was better associated with all-cause/CVD mortality in patients with diabetes compared to other body metabolic indices. Conclusions In patients with diabetes, we found an association between BRI and all-cause/CVD mortality.